Medan Amusement Center (Hi-Tech Architecture) - Andalucia .; Minadiah Purba (Talenta Publisher, 2018)
From the Central Bureau of Statistics (2014) survey for the happiness index according to the province, North Sumatra is ranked 6th lowest. This data was becoming the basis of the design background of the Medan Amusement Center. Where has, the design in the city becomes a solution due to the distance to the people of Medan for recreation, aims to save time, cost and want to build a city image. Accordingly, the design of the Medan Amusement Center, which located at Jendral Abdul HarisNasution is adjacent to the access to the Kuala Namu International Airport. The design aims to give a new face or Landmark, then the design of the Amusement Center should be an icon for easy to remember. Therefore, the theme applied to the design is High Tech where the theme gives the impression of Futuristic with the use of materials and structures.